Booker T. Washington - Flynn, Riley (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2014)
"Simple text and photographs present the life of Booker T. Washington"--
Includes bibliographical references (page 23) and index.
Keywords: Washington, Booker T., -- 1856-1915 -- Juvenile literature; Washington, Booker T., -- 1856-1915; African Americans -- Biography; Educators -- Biography -- United States; African Americans; Educators